Predictors of virological failure in HIV‐1‐infected patients switching to dolutegravir maintenance monotherapy. Issue 1 (30th September 2018) - Wijting, IEA; Rutsaert, SL; Rokx, C; Burger, DM; Verbon, A; van Kampen, JJA; Boucher, CAB; Rijnders, BJA; Vandekerckhove, L
Abstract : Objectives: The Dolutegravir Monotherapy for HIV (DOMONO; NCT02401828) study showed that maintenance monotherapy with dolutegravir (DTG) is associated with virological failure (VF) and leads to DTG resistance and as a result should not be used. However, data on clinical and virological factors associated with VF during DTG monotherapy are lacking. We identified factors associated with VF during DTG monotherapy. Methods: A randomized trial was carried out in which patients on combination antiretroviral therapy (cART) with an HIV‐1 RNA zenith < 100 000 copies/mL and a CD4 T‐cell nadir ≥ 200 cells/μL, who had never experienced VF, switched to DTG monotherapy. Clinical and virological factors were compared between patients with and without VF, using univariate analyses. Results: Eight of the 95 patients developed VF during DTG monotherapy. A total of 78 participants had reached week 48 when the study was discontinued. The median CD4 T‐cell nadir was lower in patients with VF than in patients without VF [260 (interquartile range (IQR) 223–320) versus 380 (IQR 290–520) cells/μL, respectively; P  = 0.011]. Patients with VF had a longer time between HIV diagnosis and cART initiation than those without VF [median 49 (IQR 27–64) versus 15 (IQR 1–38) months, respectively; P  = 0.015]. The median total peripheral blood mononuclear cell (PBMC) HIV DNA copy number was higher in patients with VF than in those without VF [417 (range 85–4151) versus 147 (range 16–4132) copies/10 6 PBMCs, respectively; P  = 0.022]. Conclusions: A lower CD4 nadir, a longer time between HIV diagnosis and cART initiation, and a higher HIV DNA copy number at the time of DTG monotherapy initiation were associated with VF. While there clearly is no future role for DTG monotherapy, ongoing and future studies on the efficacy of maintenance dual therapy (e.g. DTG lamivudine) may have to take these variables into account in their study design and analysis.